Housing and the business cycle revisited - Daniel Fehrle (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2018)
In this paper, I present a multi-sectoral DSGE-model with housing, real rigidities and variable capital utilization that generates aggregate and sectoral co-movements due to sector specific shocks. Furthermore, the model accounts for two puzzles: First, residential investment correlates positively with house prices, and second, GDP residential and business investment tend toward the empirically observed lead-lag pattern. I show that, except for relative prices, all co-movements and the lead-lag pattern of different investment types are endogenous in the calibrated model and independent of the properties of the shock. In a second step, I estimate these properties with Bayesian techniques. As it turns out, shocks to sectors with similar elasticities in the final good sectors play a role related to aggregated shocks. In contradiction to a standard assumption in the literature, shocks to the construction sector seem to be lower than others.
Keywords: E13; E32; O41; R31; 330; Housing market; sectoral and aggregate co-movements